Do palhaço à palhaformance: uma poética da presença do palhaço em performance - Teles, Tiago Gonçalves (2016)
The main objective of the present project is to construct the Clown's personal poetics within the context of Visual Arts, through Performance Art. Such matter brings the Clown closer to various proposals and thoughts that are unique to contemporary art where Performance Art is inserted. Therefore, this intent encourages thinking and going after the establishment of contact points between Clown Art and Visual Arts, unders the prism of Performance Art, for the elaboration of what the researcher-artist has been calling "Clownperformance" or "Clownformance". Also, this course seeks to think and discuss the presence of the Clown being in that poetics as a cultural and counter-cultural manifestation, simultaneously. Thus were constructed the understandings on the concepts ofClown, Visual Arts - Performance - and Being/Presence. Therefore, the motivations that support the investigation reside in the first question, which is: Who is the Clown? The selected authors to reference the understandings on the Clown were Dimitri, Burnier, Bolognesi and Dario Fo, artists with experiences relevant to Clown art, plus researchers in the universe that involves this practice. The second point that sustains the investigation in course refers to the Visual Arts, especially Performance Art. In the present work, the discussions about Performance Art are founded by the studies of Goldberg, Cohen, Taylor and Schechner. Their researches on the origin and characteristics of Performance Art contribute to the proponent's construction of contact points between Clown Art and Performance Art in his poetics. The third point lies in the Being and the Presence of the Performing Clown. To aid with the understanding of Being/Presence, Gumbrecht's concepts were studied. The methodological procedures are anchored to the aforementioned postulates which sustain the artist's laboratorial incursions through the poetics proposed by the research. Within that perspective, seven performances took place: "A Door between two Clowns", "Dress/Deny", "Dress/Deny II the Clownvirtuality of presence", "For the end of 'white' and 'august'", "Stolen Kiss", "Paper Ball War" and "Everyday Actions". After the practices, reflections are set in motion in an attempt to organize, punctuate and clarify which central points compose a "Clownformance". On that development, we turned to Eleonora Falcão and Demiam Morira Reis to help think of a possible "Clownformance" dramaturgy, to Nassim Nicholas Taleb to reflect upon the unlikely and to Sun Tzu for the important task of clearing up subversion. It is fundamental to point out that this project has no pretension of being a manual on how to create poetics. On the contrary, its contribution lies in sharing a path toward the development of a poetics of its own from the researcher' restlessness, given that every artist has his own latent restlessness.